2006
DOI: 10.1111/j.1399-3046.2006.00521.x
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of nocturnal hypertension in pediatric renal allograft recipients*

Abstract: Hypertension is common in children with end-stage renal disease who have undergone renal transplantation. We performed ambulatory blood pressure monitoring (ABPM) in renal allograft recipients who were on stable maintenance immunosuppressive medications and were more than six months post-transplant. Echocardiographic measurement of left ventricular mass index (LVMI) was obtained at the time of ABPM. Twenty-nine children with a mean age of 14.8 yr (8-18 yr) were evaluated 4.3 yr (0.6-12.8 yr) after deceased don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 34 publications
7
46
0
1
Order By: Relevance
“…Similar to that in other pediatric studies, we found that daytime hypertension in renal TX children occurred in conjunction with night-time hypertension [45][46][47]. Although the significance of night-time hypertension as a predictor of CV risk is not well elucidated in children post-TX, in studies on adults with hypertension, nocturnal hypertension is a better predictor of cardiovascular events than daytime BP [48].…”
Section: Discussionsupporting
confidence: 84%
“…Similar to that in other pediatric studies, we found that daytime hypertension in renal TX children occurred in conjunction with night-time hypertension [45][46][47]. Although the significance of night-time hypertension as a predictor of CV risk is not well elucidated in children post-TX, in studies on adults with hypertension, nocturnal hypertension is a better predictor of cardiovascular events than daytime BP [48].…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies in pediatric transplanted patients accentuated importance of ABPM for detection of nocturnal hypertension [16,23]. As in these studies, ABPM revealed a high prevalence of daytime and nighttime hypertension in pediatric allograft recipients.…”
Section: Discussionsupporting
confidence: 50%
“…Studies show the prevalence of masked hypertension (normal office BP and elevated ABPM) was 50% greater than that identified using casual BP [98][99][100][101] and an increased prevalence of nondippers among children with kidney transplants. 101,102 A study by Polónia et al 103 concurs with other studies showing significant rates of nocturnal hypertension in pediatric transplant recipients and that a significant proportion of patients thought to be adequately controlled by medications still had masked hypertension.…”
Section: Hypertension In the Pediatric Transplant Recipient Or Recipimentioning
confidence: 66%